IN VITRO ACTIVITY OF ENROFLOXACIN AGAINST CLINICAL ESCHERICHIA COLI AND NON-LACTOSE FERMENTING ENTEROBACTERIA ISOLATES FROM CHICKENS IN BENUE STATE, NIGERIA - Jamilu, R. Y.; Asambe, A. (FUDMA JOURNAL OF SCIENCES, 2021)
Clinical bacterial isolates from chickens were analysed to determine their susceptibilities to antimicrobial agent. Ten (10) Escherichia coli and 8 non lactose fermenting Enterobacteriaceae species isolated from a pool of clinical cases of chickens from Microbiology Laboratory of the Veterinary Teaching Hospital, University of Agriculture Makurdi were used for the study. Enrofloxacin with 99 % purity obtained from Sigma-Aldriech, USA and prepared in varying concentrations (0.1 - 50μg/mL) was used in vitro by Kirby-Bauer’s disc-diffusion method. The isolates were susceptible to enrofloxacin at a minimum concentration of 25 (μg/mL) and the mean value in the zones of inhibition exhibited by Escherichia coli and non-lactose fermenters were significantly different (p
Keywords: Antibacterial, Chicken, Enrofloxacin, Escherichia coli, Non-lactose fermenter